Factors influencing aflatoxin biomarker level in urine among adults in Hulu Langat District, Selangor, Malaysia - Sulaiman, Siti Husna (2017)
Previously, there were several cases related to aflatoxin occurred in Malaysia. Aflatoin is commonly found in human food resources especially in nuts, cereals, poultry and livestock, and the impact of this food-borne poisoning should be taken seriously. This study involved a total of 468 adults who resided in Hulu Langat district and aged from 18 to 60 years old. Data on socio-demography (SD) knowledge, attitude and practice (KAP) on aflatoxin and its contamination in food, dietary intake (DI), physical activity (PA) and weight status (WS) through the questionnaires and 15ml of non-fasting morning urine samples were collected to measure the aflatoxin level. The quantification of urinary aflatoxin M1 (AFM1) was done using ELISA kit. Statistical analysis involved descriptive analysis and inferential analysis. Of the 468 screened respondents, 444 met the following study criteria: in good health; not taking any medications or supplements; not smoking; not following a restricted diet; not pregnant and not in postpartum period. There were 249 females and 199 males of which majority of them aged between 18 to 24 years old with an average age of 29.21 years old. More than half of the respondents were single (n= 320) and had RM1500 or less amount of personal income (n=303). There were 238 respondents had low knowledge, 178 respondents had positive attitude while 209 respondents had positive practice towards aflatoxin. A total of 281 respondents had a normal BMI with majority of them (n=190) practised a low level of physical activity. Cereal and cereal-based products recorded the highest food consumption among respondents with an average intake of 512.54g/day. From 444 samples, 199 were positive with AFM1 with 37 of them exceeded the limit of detection (LOD) of 0.64ng/mL. The statistical analysis showed significant associations in aflatoxin level based on age group (p<0.05), ethnicity (p<0.01) and household income (p<0.01), attitude (p<0.01) and practice (p=0.03) towards aflatoxin and its contamination in food, intake of eggs (p=0.03) and milk and dairy products (p<0.01). Besides, the binomial logistic regression showed ethnicity, household income and intake of dairy products were factors that contributed to aflatoxin occurrence in urine with ethnicity (W=25.57, p<0.01) as the main predictor. Chinese were 3.20 times more likely to exhibit aflatoxin occurrence in urine compared to non-Chinese. When both husband and wife are working, the household income increases and encourages the eating-out activity. Eating-out exposes consumers to aflatoxin contamination, as not all food premise owners care about the presence and danger of this toxin to humans. Chinese were having the highest levels of urinary aflatoxin due to high intake of potentially aflatoxin-contaminated foods such as cereals, nuts, milk and eggs. This research was one of the first steps in increasing the awareness towards aflatoxin among adults in Hulu Langat district, Selangor. Findings from this research showed the current level of aflatoxin among Malaysians in Hulu Langat and the factors that might influence the aflatoxin presence in human based on the aflatoxin biomarker level.